Expression of the major core structural proteins VP3 and VP7 of African horse sickness virus, and production of core-like particles. - Maree, S; Durbach, S; Maree, F; Vreede, F; Huismans, H (1998)
The genome segments encoding the seven structural proteins of African horse sickness virus (AHSV), including the largest coding for VP1, were cloned and sequenced. Analysis of the VP1 sequence supports the putative identity of this protein as an RNA polymerase. The genes encoding the two major core proteins, VP3 and VP7, were also cloned and expressed by both in vitro translation and by means of recombinant baculoviruses. Co-infection of insect cells with VP3 and VP7 recombinant baculoviruses resulted in the intracellular formation of multimeric particles with a diameter of 72 nm, which structurally resembled authentic AHSV cores (core like particles: CLP). The complete genome of AHSV has now been cloned and sequenced.